THE ROLE OF ZANZIBAR IMPROVING STUDENTS’ PROSPECT (ZISP) PROJECT IN ADVANCING TEACHERS’ KNOWLEDGE AND SKILLS - Massoud Hamad, Hamad; Massawe, Goodluck; Nyinondi, Onesmo (International Online Journal of Education and Teaching, 2025)
Education is one of the key elements in a country’s development. Therefore, Teacher Professional Development (TPD) has long been promoted as a means to foster the adoption of teaching methods. Tanzania and Zanzibar Governments have implemented several initiatives to improve the quality of education. The ZISP project was a five (5) years project from 2016 to 2021, funded by the World Bank and implemented in Zanzibar. The research objective was to assess the role of ZISP in enhancing teachers’ knowledge and skills and identify challenges teachers face. A cross-sectional study design was employed, and data was collected from 69 trainees using a semi-structured questionnaire. Quantitative data were analysed descriptively, focusing on percentages and frequencies, and inferentially using the Wilcoxon signed rank test. Qualitative data collected were analysed using Thematic Analysis. The study’s findings have shown that the ZISP Project improved teachers’ knowledge and skills in pedagogy, subject matter, and challenges teachers face. In conclusion, the results of the study indicate a significant enhancement in teachers’ knowledge and skills, particularly in pedagogy and subject matter knowledge. It is recommended that the government and the development partners should prepare a similar project like ZISP and expand the projects to include teachers from all subjects.